Federal Building and Lakes of the Nations, California World's Fair on San Francisco Bay (Stanley A. Plitz Company)
Fronting on the Lakes of the Nations is the $1,500,000 Federal Building. In its center is the Colonnade of the States, comprising forty-eight closely grouped 104 foot columns. The World's largest murals cover the front walls -350 feet long by 60 feet high each - and tell the story of the conquest of the West.